Dissimilarities of Shallot (Allium ascalonicum L.) Seedlings Growth and Quality through Priming with Moringa Leaf Extract - Muhammad Faried; Elkawakib Syam'un; Katriani Mantja (Kufa Journal for Agricultural Sciences)
Seed priming is one method for increasing the growth and quality of seedlings. This study aims to evaluate moringa leaf extract as a priming agent and its effect on the seedling growth and quality of shallot from true seed. This study used a randomized block design with five replications. Priming treatment consisted of unprimed, hydropriming, and three levels of Moringa leaf extract concentration, including 12.5%, 25%, and 37.5%. A one-way analysis of variance was used to perform statistical analysis, with a p-value of 0.05 considered significant. In addition, the mean comparison was performed by Tukey multiple comparison test. According to the research, seed priming with moringa leaf extract at 37.5% resulted in the best effects on the parameter seedling emergence index (1.20), plant height (31.12 cm), number of leaves (4.80), pseudo stem diameter (3.22 mm), total root length (329.70 mm), number of root tips (94.60), root volume (4.64 mm3), fresh weight seedling (2.77 g), dry weight seedling (0.19 g) and seedling quality index (0.0126), while compared to other treatments.